Impacto educacional em saúde e segurança no trabalho decorrente dos encontros regionais de CIPAs - Caetano, Raphael Perini [UNESP]; Romanini, Gabriel Hortensi [UNESP]; Barbosa, Renata Trasse de Oliveira [UNESP]; Rodrigues, Rogério de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Regulatory Standard No. 5 requires that all public and private institutions constitute the Internal Commission for Accident Prevention (CIPA) as a fundamental guideline in accident prevention and health promotion. The Education Extension Project in occupational health developed, in conjunction with the Occupational Health Reference Center (CEREST), in the years 2011 to 2014, four training cycles to accident prevention commission of Single Island region, called Regional CIPAS meeting with the to assisting professionals in the direct prevention of accidents and injuries in workers' health. To evaluate the results of the events were analyzed the participants' profile by industry, just like said auto use in the courses taken reaction assessment. The results show that the event reached different categories of organizations and cities in the region, and contribute directly to the instrumentalization of professionals to carry out accident prevention commission assignments. Also he points out the pioneering University to develop enhanced training activities in the theme and its due contribution to Public Health.

A Norma Regulamentadora nº. 5 estabelece que todas as instituições públicas e privadas constituam a Comissão Interna de Prevenção de Acidentes (CIPA) como diretriz fundamental na prevenção de acidentes e promoção de saúde. O Projeto de Extensão Educação em Saúde no Trabalho desenvolveu, em conjunto com o Centro de Referência em Saúde do Trabalhador (CEREST), nos anos de 2011 a 2014, quatro ciclos de capacitação aos Cipeiros da região de Ilha Solteira, denominados Encontro Regional de CIPAS, com o objetivo de subsidiar os profissionais na prevenção direta de acidentes e agravos na saúde do trabalhador. Para avaliação dos resultados dos eventos foi analisado o perfil dos participantes por ramo de atividade, bem como o aproveitamento auto referido nos cursos realizados em avaliação de reação. Os resultados apontam que o evento atingiu diferentes categorias de organizações e cidades da região, além de contribuir diretamente na instrumentalização dos profissionais para o exercício das atribuições dos Cipeiros. Também apontam o pioneirismo da Universidade em desenvolver ações de formação ampliada na temática e sua decorrente contribuição para a Saúde Pública.
Keywords: Security; Education; Public health; Segurança; Educação; Saúde pública